(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, opinions are given about the importance of art-pedagogical tools in the military-patriotic education of students, the organization of spiritual and educational events with the help of museums, theater and cinema, as well as the importance of theater art in the education of young people.